Framework for Brain Computer Interface implemented to control devices in the context of home automation - Ierache, Jorge Salvador (2013)
This paper presents the device controlling using brain machine interface (BMI), through the development of a Framework implemented for the acquisition, configuration and control in the context of home automation.